2015
DOI: 10.1589/jpts.27.2921
|View full text |Cite
|
Sign up to set email alerts
|

The effects of computer-assisted cognitive rehabilitation on Alzheimer’s dementia patients memories

Abstract: [Purpose] The purpose of the present study was to conduct Computer-Assisted Cognitive Rehabilitation (COMCOG) to examine the effects of COMCOG on Alzheimer’s dementia patients’ memories. [Subjects] Thirty-five patients diagnosed with Alzheimer’s dementia received COMCOG for 30 minutes per day, five days per week for four weeks. [Methods] Before and after the COMCOG intervention, subjects’ cognitive functions were evaluated using the Cognitive Assessment Reference Diagnosis System (CARDS) and Mini-Mental State … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
9
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 7 publications
2
9
0
1
Order By: Relevance
“…We found 19 studies in which 11 digital cognitive training programs for older people with cognitive impairment and dementia were mentioned. The selected papers consisted of ten RCTs (Gaitán et al, 2012;Zaccarelli et al, 2013;Fiatarone Singh et al, 2014;Barban et al, 2015;Cavallo et al, 2016;Hyer et al, 2016;Suo et al, 2016;Bahar-Fuchs et al, 2017;Hagovská et al, 2017;Cavallo and Angilletta, 2018), five pre-post studies (Gigler et al, 2013;González-Palau et al, 2014;Hwang et al, 2015;Vermeij et al, 2017;Mendoza Laiz et al, 2018), two studies with repeated measures design (Eckroth-Bucher and Siberski, 2009;Vermeij et al, 2016), one pilot study (Danassi, 2015), and one study protocol for an RCT (Vanova et al, 2018).…”
Section: Characteristics Of Computerized Programsmentioning
confidence: 99%
See 1 more Smart Citation
“…We found 19 studies in which 11 digital cognitive training programs for older people with cognitive impairment and dementia were mentioned. The selected papers consisted of ten RCTs (Gaitán et al, 2012;Zaccarelli et al, 2013;Fiatarone Singh et al, 2014;Barban et al, 2015;Cavallo et al, 2016;Hyer et al, 2016;Suo et al, 2016;Bahar-Fuchs et al, 2017;Hagovská et al, 2017;Cavallo and Angilletta, 2018), five pre-post studies (Gigler et al, 2013;González-Palau et al, 2014;Hwang et al, 2015;Vermeij et al, 2017;Mendoza Laiz et al, 2018), two studies with repeated measures design (Eckroth-Bucher and Siberski, 2009;Vermeij et al, 2016), one pilot study (Danassi, 2015), and one study protocol for an RCT (Vanova et al, 2018).…”
Section: Characteristics Of Computerized Programsmentioning
confidence: 99%
“…The study found an increase in picture recognition and concepts in both groups. Hwang et al (2015) conducted a pre-post study to examined the effects of the cognitive rehabilitation program ComCog on the global cognition of people with Alzheimer's Disease and concluded that participants performed better on orientation and information registration while no improvements in recognition were observed.…”
Section: Cognitive Rehabilitation Programsmentioning
confidence: 99%
“…La rehabilitación cognitiva de las personas con demencia tiene sus peculiaridades propias ya que se trata de ralentizar, en la medida de lo posible, un deterioro cognitivo que tiende a ser progresivo. El efecto positivo de la rehabilitación cognitiva basada en ordenador se ha observado en personas con enfermedad de Alzheimer, siendo capaz de retrasar el deterioro de la memoria (Crete-Nishihata et al, 2012;Hwang, Cha, Cho, Kim y Cho, 2015). Un reciente metaanálisis indica que las intervenciones cognitivas basadas en ordenador fueron más beneficiosas que aquellas intervenciones no basadas en ordenador (García-Casal et al, 2016).…”
Section: Rehabilitación Cognitiva Por Ordenadorunclassified
“…Professionals and researchers in the cognitive rehabilitation arena are dedicated to the creation and advancement of interventions that are efficacious, cost-effective, easily administered and applicable to large numbers of patients across different levels of impairment. 1 Computer-based rehabilitation programmes (CBRP) are very promising as they offer high levels of customisation, applicability and familiarity. 2 …”
Section: Introductionmentioning
confidence: 99%